Estimation and Distribution of Some Heavy Metals in Urban Soils at Kufa, Najaf Governorate: An Environmental Geochemistry Research - Muslim, Ruaa I.; Al-Ankaz, Zinah S.; Al-Owaidi, Mohanad R. A. (Iraqi Journal of Science, 2023)
Kufa, considered one of the important cities in Iraq, is facing a rapid increase in population proportion and urban development in buildings and industry. Therefore, the concentration of several hazardous heavy metals is the main focus of this study. It presents the distribution and Estimation of heavy metals in urban lands in the Kufa area as an environmental geochemical study. Twenty samples of urban surface soils were collected in many sites to determine concentrations, distribution, and contamination of elements Cu, Zn, Co, Ni, Th, U, Pb, Hf, Nb, and Fe. The mean concentrations of heavy metals were compared with the local studies, UCC guidelines, and the world reference. To distinguish anthropogenic pollution, EF and Igeo guides were calculated. The obtained results established that contamination in Kufa soil land was slightly polluted by U (2.83ppm) and Nb (10.81ppm) and moderately polluted by Pb (31.7ppm) and Hf (9.75ppm). The research revealed that the reason for the elevation in the lead in the Kufa soil is that it often suffers from severe vehicle overcrowding during religious occasions.